Perlindungan Hukum Dan Penyelesaian Sengketa Terhadap Pemenang Lelang Yang Tidak Dapat Menguasai Objek Lelang - M Rizal Fattabania; Maryano Maryano; Yurisa Martanti (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2022)
The object of the mortgage guarantee is regulated in Article 6 of Law Number 4 of 1996. In practice, discrepancies have been found regarding the auction. Many auction winners cannot control the auction objects they have won. The method used in this research is the normative legal method with the type of normative juridical research, namely library law research or secondary data with primary, secondary and tertiary legal sources. From the results of the study, it can be obtained that dispute resolution can be carried out through litigation and non-litigation and legal protection of the auction winner in article 25 PMK 213/PMK.06/2020 auctions that have been carried out in accordance with the provisions of the legislation, cannot be canceled. Therefore, if the winner of the auction cannot control the object, he can sue through litigation or non-litigation and legal protection here should be if the winner of the auction has been determined then the object of the auction has been owned.Keywords: Mortgage; Auction; Dispute Resolution; Legal Protection AbstrakObjek jaminan hak tanggungan diatur dalam pasal 6 Undang-Undang Nomor 4 tahun 1996. Dalam praktik ditemukan adanya ketidaksesuaian mengenai lelang. Banyak pemenang lelang tidak dapat mengusai objek lelang yang telah dimenangkannya. Metode yang digunakan dalam penelitian ini adalah metode hukum normatif dengan jenis penelitian yuridis normative, yaitu penelitian hukum kepustakaan atau data sekunder dengan sumber bahan-bahan hukum primer, sekunder dan tersier. Dari hasil penelitian dapat diperoleh yaitu penyelesaian sengketa dapat dilakukan melalui jalur litigasi dan non litigasi dan perlindungan hukum pemenang lelang dalam pasal 25 PMK 213/PMK.06/2020 lelang yang telah dilaksanakan sesuai dengan ketentun peraturan perundangan-undangan, tidak dapat dibatalkan. Oleh karena itu pemenang lelang jika tidak bisa menguasai objeknya dapat menggugat melalui jalur litigasi maupun jalur non litigasi dan perlindungan hukum disini seharusnya jika pemenang lelang sudah ditentukan maka objek lelang telah dimiliknya.Kata Kunci: Hak Tanggungan; Lelang; Penyelesaian Sengketa; Perlindungan Hukum